2015
DOI: 10.11113/ijbes.v2.n1.56
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Urban Heat Island under the Hanoi Master Plan 2030 on Cooling Loads in Residential Buildings

Abstract: This study aims to evaluate the influence of urban heat island (UHI) under the Hanoi Master Plan 2030 on the energy consumption for space cooling in residential buildings. The weather conditions under the current and future status (master plan condition) simulated in the previous study (Trihamdani et al., 2014) were used and cooling loads in all the residential buildings in Hanoi over the hottest month were estimated under the simulated current and future conditions by using the building simulation program, TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In 2010, the Vietnamese building sector accounted for 20 to 24% of the total national energy use, which is expected to increase significantly, especially due to increased AC use (Nguyen et al 2011 ; Le Phan and Yoshino 2010 ). From 1998 to 2008, the nationwide electricity consumption increased by 400%, in which the electricity consumption for administration and household accounts made up the largest proportion (Nam et al 2015 ). This development is mostly driven by income growth and poor building design, but also by increasing heat exposure due to urban growth.…”
Section: Challenges With Air Conditioningmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2010, the Vietnamese building sector accounted for 20 to 24% of the total national energy use, which is expected to increase significantly, especially due to increased AC use (Nguyen et al 2011 ; Le Phan and Yoshino 2010 ). From 1998 to 2008, the nationwide electricity consumption increased by 400%, in which the electricity consumption for administration and household accounts made up the largest proportion (Nam et al 2015 ). This development is mostly driven by income growth and poor building design, but also by increasing heat exposure due to urban growth.…”
Section: Challenges With Air Conditioningmentioning
confidence: 99%
“…The high-rise apartment blocks and detached houses are built to rely entirely on AC and little attention is paid to build in an energy-efficient manner (Le Phan and Yoshino 2010 ). The connection between design and the escalation of energy consumption for cooling has been shown to be significant, especially when considering the effects of urbanisation and rising urban temperatures (Nam et al 2015 ). The increasing use of AC combined with global trends in urban and building design enforces a growing urban heat vulnerability as well as increased emission of greenhouse gases.…”
Section: Challenges With Air Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…How will the Master Plan impact Hanoi's overall environmental conditions? Nam et al [30] evaluated the influence of UHI under the Hanoi Master Plan 2030 on the energy consumption for space cooling in residential buildings. They found that the increments in built-up areas were larger than those in existing built-up areas, and that the cooling load in an apartment is approximately half of that in a detached house, which itself approximately half of that in a row house.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature survey, state-of-the-art of correlations between UHI or SUHI and land-use composition are being widely analyzed in the recent years. In contrast, the study of UHI or SUHI with respect to Hanoi City Master Plan 2030 is rather limited; for example, about spatial energy consumption [30], assessment of UHI effects based on WRF simulations [31]. Then, what would be the most updated status of land use change with respect to the city Master Plan?…”
Section: Introductionmentioning
confidence: 99%